Membangun Kesadaran Green Economy melalui Pulau Plastik dengan Kecerdasan Ekokritik Sastra - Rosita Sofyaningrum; Bagiya Bagiya; Karina Sistiyaningrum (Balai Bahasa Provinsi Bali, 2024)
This research highlights the importance of supporting and disseminating the concept of green economy as a critical step towards the sustainability of human life on this planet. The main focus of this study is to analyze the usage of plastic and the damage caused by plastic waste, as illustrated in the documentary film